2020
DOI: 10.1177/1039856220905304
|View full text |Cite
|
Sign up to set email alerts
|

No country for older men: ageing male suicide in New Zealand

Abstract: Objective: Suicide rates increase in late life. There is, however, a gap in understanding suicide in the very old. We aimed to underscore the evidence for high rates of death by suicide in the oldest-old men (age 85+) in New Zealand and to provide a conjectural discussion about factors driving these rates. Method: Provisional suicide data were obtained from the New Zealand Coronial Services website for the period 2011–2019. Yearly suicide rates for those aged 85+ were plotted over time. Mean suicide rates were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 22 publications
0
11
0
3
Order By: Relevance
“…The effects of it lasted for the following years, since it was found that the suicide rates did not return to preepidemic rates [25]. In New Zealand, suicide rates of older men aged 85 years and above between 2011 and 2019 were the second highest amongst all age groups [26]. The social isolation and loneliness to which older adults are exposed during the COVID-19 pandemic in New Zealand could have important implications in increasing the already high suicide rates.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of it lasted for the following years, since it was found that the suicide rates did not return to preepidemic rates [25]. In New Zealand, suicide rates of older men aged 85 years and above between 2011 and 2019 were the second highest amongst all age groups [26]. The social isolation and loneliness to which older adults are exposed during the COVID-19 pandemic in New Zealand could have important implications in increasing the already high suicide rates.…”
Section: Discussionmentioning
confidence: 99%
“…24,25,26 However, suicide rates have been found to increase with age in most western and developed nations. 27,28 The difference may be because of life expectancy which is lower in most low-and middle-income countries. 29 Several factors, such as difficulty to cope with adversity or social problems, limited resources and network, may be contributing to higher rates of suicidal behaviour amongst young people, unlike older adults who probably have a stable network of resources.…”
Section: Age and Suicidal Behaviourmentioning
confidence: 99%
“…over 65 years) being at highest risk. Globally, older men are twice as likely to die by suicide compared to women in the same age groups (Barak et al, 2020;Canetto, 2017). Suicide ideation (thoughts, desires, or plans surrounding ending one's own life) is a recognized risk factor in suicidal behavior (Nock et al, 2008) and increases the risk accurately and routinely screen for suicide ideation.…”
Section: Introductionmentioning
confidence: 99%